2019
DOI: 10.1519/jsc.0000000000001888
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Bone Mineral Density of Division 1 Collegiate Football Players: A Consortium of College Athlete Research Study

Abstract: The purpose of the present study was to generate normative data for total and regional body composition in Division 1 collegiate football players using dual-energy X-ray absorptiometry (DXA) and examine positional differences in total and regional measurements. Data was used from the Consortium of College Athlete Research (C-CAR) group. Four hundred-sixty-seven players were included in this study. Height, weight, total and regional fat mass, lean mass and bone mineral density were measured in each athlete in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
61
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 28 publications
10
61
0
7
Order By: Relevance
“…vances in DXA technology allow for quantification of visceral adipose tissue (VAT)-fat mass located within the abdominal region, with higher amounts associated with a greater cardiometabolic disease risk [4][5][6]. While previous studies have examined VAT in both professional and collegiate football players and normal weight young adults [2,7,8], no studies to date have reported VAT mass for baseball players.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…vances in DXA technology allow for quantification of visceral adipose tissue (VAT)-fat mass located within the abdominal region, with higher amounts associated with a greater cardiometabolic disease risk [4][5][6]. While previous studies have examined VAT in both professional and collegiate football players and normal weight young adults [2,7,8], no studies to date have reported VAT mass for baseball players.…”
Section: Resultsmentioning
confidence: 99%
“…To date, no studies have examined baseball players' VAT mass. Notably, previous studies have only examined VAT mass in professional [7] and collegiate football players [2] and in young adults [8,24]. In a previous study [24] conducted in males and females aged 19-47 years, VAT mass was shown to significantly increase once individuals reached a particular percent body fat threshold.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Higher amounts of VAT have been associated with greater cardiometabolic disease risk [3,8,20]. Whereas previous studies have examined VAT in professional and collegiate football players [2,6] and normal weight young adults [5], no studies to date have examined VAT mass in female athletes or, specifically, female equestrian athletes.…”
Section: Introductionmentioning
confidence: 99%